Academic partnerships with clinical nurse scientist mentors improve the Doctor of Nursing Practice student experience - Margaret A. Gettis; Kelly Winter; Christina J. Calamaro (Journal of the American Association of Nurse Practitioners, 2026)
ABSTRACT The Doctor of Nursing Practice (DNP) degree has become firmly established as the terminal practice degree for advanced practice registered nurses in the United States. A defining component of the DNP curriculum requires students to implement a scholarly project that addresses a clinical problem and improves patient or system outcomes. This article describes the development and implementation of a structured clinical–academic partnership between a university-based DNP nurse anesthesia program and a pediatric health care organization in the southeastern United States. Central to this collaboration was the establishment of the clinical Nurse Scientist Mentor (NSM) role designed to bridge academic and clinical environments. To develop high-level DNP student projects, the NSM and academic faculty connected the DNP student-employees to projects that improved patient, clinical, or system outcomes. The experience in this report suggests that structured clinical–academic partnerships can strengthen the quality, relevance, and sustainability of DNP scholarly work. In addition, the NSM is an innovative and viable model that can be replicated in health care systems where DNP projects are being implemented.